2018
DOI: 10.3897/phytokeys.103.25392
|View full text |Cite
|
Sign up to set email alerts
|

Begonia medogensis, a new species of Begoniaceae from Western China and Northern Myanmar

Abstract: Begonia medogensis JianW.Li, Y.H.Tan & X.H.Jin, a new species of Begoniaceae, is described and illustrated by colour photographs. Begonia medogensis is distributed in western China and northern Myanmar. It has erect stems, is tuberless, has many triangular to lanceolate leaves, base slightly asymmetric, margins remotely and irregularly denticulate; staminate flowers have 4 perianth segments, with outer 2 segments broadly ovate, inner 2 spathulate; pistillate flowers have 5 perianth segments, unequal, outer 4 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…China has over 210 accepted names of Begonia and its southwest region is one of the distribution centres of this genus. In the past two years, ten Begonia species were newly described (Chen et al 2018a(Chen et al , 2019Ding et al 2018;Li et al 2018Li et al , 2019He et al 2019;Tong et al 2019;Wang et al 2019a) and many more are likely awaiting discovery and description in China. At the same time, several newly-recorded Chinese Begonia species (Yang et al 2015;Wang et al 2019b) and synonyms (Shui and Chen 2017;Chen et al 2018b) have also recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…China has over 210 accepted names of Begonia and its southwest region is one of the distribution centres of this genus. In the past two years, ten Begonia species were newly described (Chen et al 2018a(Chen et al , 2019Ding et al 2018;Li et al 2018Li et al , 2019He et al 2019;Tong et al 2019;Wang et al 2019a) and many more are likely awaiting discovery and description in China. At the same time, several newly-recorded Chinese Begonia species (Yang et al 2015;Wang et al 2019b) and synonyms (Shui and Chen 2017;Chen et al 2018b) have also recently been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Located in southeastern Xizang, Medog County is one of the biodiversity hotspots in China, which has rich plant diversity in the Eastern Himalaya (Sun and Zhou 1996). Recently, new taxa of seed plants have continuously added to the flora of this region (Li et al 2018;Li et al 2021;Tian et al 2021;Ya et al 2021;Zhou et al 2021). Previous taxonomic studies on the ferns in Xizang have partially uncovered the fern diversity in Medog (Wu 1983;Ling 1984a, 1984b;Zhang et al 2004); recent work has added more new species and new records to the fern flora of this region (Wei et al 2018;Fan et al 2021;Qiu et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are restricted to the southwestern region of the country, which is a designated biodiversity hotspot. Many new species have been discovered and described from this region in recent years (Zhang et al 2017, Cai et al 2018, Li et al 2018, Xin et al 2018, Yang et al 2018, including Impatiens (Yu et al 2009, Bi et al 2010, Hou et al 2011, Kuang et al 2014, Luo et al 2014, Tan et al 2015, Cho et al 2017.…”
Section: Introductionmentioning
confidence: 99%